2013
DOI: 10.1186/1754-6834-6-172
|View full text |Cite
|
Sign up to set email alerts
|

Comparative secretome analysis of Trichoderma asperellum S4F8 and Trichoderma reesei Rut C30 during solid-state fermentation on sugarcane bagasse

Abstract: BackgroundThe lignocellulosic enzymes of Trichoderma species have received particular attention with regard to biomass conversion to biofuels, but the production cost of these enzymes remains a significant hurdle for their commercial application. In this study, we quantitatively compared the lignocellulolytic enzyme profile of a newly isolated Trichoderma asperellum S4F8 strain with that of Trichoderma reesei Rut C30, cultured on sugarcane bagasse (SCB) using solid-state fermentation (SSF).ResultsComparison of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 59 publications
3
57
1
4
Order By: Relevance
“…Xylanase activities reported in earlier studies were very poor in the range 14. U/gds (Marx et al 2013) and 162 U/mL (Asad et al 2015), which is the highest xylanase activity ever reported prior to this study. Finding in this study therefore suggested the potential of T. asperellum for enhanced xylanase production Growth rate and the corresponding xylanase productivity by T. asperellum USM SD4 were determined.…”
Section: Optimization Of Xylanase Production By T Asperellum Usm Sd4mentioning
confidence: 75%
See 1 more Smart Citation
“…Xylanase activities reported in earlier studies were very poor in the range 14. U/gds (Marx et al 2013) and 162 U/mL (Asad et al 2015), which is the highest xylanase activity ever reported prior to this study. Finding in this study therefore suggested the potential of T. asperellum for enhanced xylanase production Growth rate and the corresponding xylanase productivity by T. asperellum USM SD4 were determined.…”
Section: Optimization Of Xylanase Production By T Asperellum Usm Sd4mentioning
confidence: 75%
“…Notwithstanding that xylanase is a principal fraction of several cell-walls degrading enzymes by which it exerts its mycoparasitic property, most studies on T. asperellum have focused on its bio-control ability at the expense of other industrial uses. Recently, both Bech et al (2015) and Marx et al (2013) separately reported a detailed proteomics of the secretome by T. asperellum to show xylanase as an important component enzyme that could be exploited for important industrial processes. However, despite their respective strides, the potential of T. asperellum as a suitable fungal isolate for enhanced xylanase has not been well exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors that improve cellulase production by T. reesei include relative humidity and temperature [28,29], continuous light exposure [27] and aeration and higher substrate concentration (Pandey, 2003) [30]. In a study performed on T. asperellum, a marginally higher endoglucanase and β-xylosidase activity was measured when it was incubated in darkness under a controlled relative humidity of 90%, compared with the standard culture without relative humidity control [10]. In the contrary, exposure to continuous light generally had a negative effect on the activity of endoxylanases and side chain hemicellulases [10].…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed on T. asperellum, a marginally higher endoglucanase and β-xylosidase activity was measured when it was incubated in darkness under a controlled relative humidity of 90%, compared with the standard culture without relative humidity control [10]. In the contrary, exposure to continuous light generally had a negative effect on the activity of endoxylanases and side chain hemicellulases [10]. This study focused on the substrate composition by changing the growth substrate to correlate it to enzyme production and enzyme diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation